THE SCOPE OF THE THEME AND THE INTERPRETATION OF THE PAINTINGS OF THE ERA - Irina, Radjabova (Журнал иностранных языков и лингвистики, 2023)
The article deals with the stylistic and formal research of such writers as I. Bunin, A. Chekhov, V. Rasputin, I. Turgenov, A. Kakhkhar, Sh. Kholmirzaev, U. Umarbekov, U. Khoshimov, in creating the plot and composition are obvious proof of our opinion. It should be noted the influence on Uzbek literature, especially artistic narration, of Ivan Turgenev, who introduced the image of a hunter into Russian narration, mastered a lot in cultural life, possessed a unique talent and mind.